An analytical discourse for utilising Terengganu’s waqf properties for human development in the state - Yusuff Jelili, Amuda (2015)
Poverty has become commonplace for many households. This unfortunate state could be a result of several challenges including the notorious financial meltdown. It could be positively argued that most governments and private and voluntary sectors have not been performing impressively towards alleviating poverty among the poor, especially in the rural areas. Waqf endowment provides human relief, dignity, financial support, and social needs to reduce poverty in society. There is a need for human development especially for the less privileged indigenous communities due to financial constraints, unemployment, and insufficient and inadequate support. The study discusses how Terengganu’s waqf properties can be used for human development such as creation of employment, micro-finance, transaction, farming, soft loans, and other lawful lucrative businesses and investments. The quantitative method is employed throughout the discussion and useful solutions to outstanding problems are suggested in the findings.